2021
DOI: 10.31466/kfbd.834252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Juglone on the Antioxidant Metabolism in the Larval Hemolymph of the Greater Wax Moth Galleria mellonella L. (Lepidoptera: Pyralidae)

Abstract: Reducing the usage of chemical pesticides used to control pests in agriculture and stored products is an important phenomenon. Also, eco-friendly biopesticides have become highly important for use in the management of the pest control programs to overcome the negative influences of other synthetic chemicals. In this study oxidative stress changes induced by one important phytochemical compound, juglone, in Galleria mellonella larvae were investigated. For this purpose, effective concentrations (LC10: 0.5 mg; L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Juglone is also used as herbicide due to its toxicity for many insects. In both samples, the major flavonoid was found to be Juglone (Dayan and Duke, 2009;McCoy et al, 2018;Erbaş and Altuntaş, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Juglone is also used as herbicide due to its toxicity for many insects. In both samples, the major flavonoid was found to be Juglone (Dayan and Duke, 2009;McCoy et al, 2018;Erbaş and Altuntaş, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…In the current study, in the testicular tissues from the Al 2 O 3 NPs group, we reported augmentations of MDA, SOD, and CAT levels, whereas the activities of TAC, GPx, CarE, and GST were substantially decreased. ErbaŞ and AltuntaŞ [ 42 ] proposed that the increase in CAT and SOD activities in G. mellonella could be attributed to an adaptive response to the oxidative damage provoked by xenobiotics. In the same manner, we suggest that the increased levels of CAT and SOD in the Al 2 O 3 NPs may arise as a spontaneous metabolic reaction to acclimatize to the agglomeration of Al inside the testicular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MDA level was heightened in the testes as a result of exposure to a single dose of Al 2 O 3 NPs, implying high lipid peroxidation. It is worth mentioning that previous investigations demonstrated that GPx functions to enhance the detoxification of lipid hydroperoxides, which stem from lipid peroxidation (LPO), and it could even hamper the instigation of LPO [ 42 ]. Therefore, the decreased levels of the antioxidant enzymes (TAC and GPx) in the testicular tissues could be explained by a rise in LPO activity that may be related to the reduction in antioxidant enzymes implicated in the detoxification of ROS in these tissues, to sustain the antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%